2007
DOI: 10.1038/sj.ejcn.1602895
|View full text |Cite
|
Sign up to set email alerts
|

Whole-grain consumption, dietary fibre intake and body mass index in the Netherlands cohort study

Abstract: Objectives: To assess the association of whole-grain and (cereal) fibre intake with body mass index (BMI) and with the risk of being overweight (BMIX25) or obese (BMIX30 kg m À2 ). Subjects: A total of 2078 men and 2159 women, aged 55-69 years, were included in the analysis, after exclusion of subjects with diagnosed cancer or deceased within 1 year after baseline or with missing dietary information. Results: We found an inverse association between whole-grain consumption and BMI and risk of overweight and obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 26 publications
4
62
1
1
Order By: Relevance
“…Alternatively, the protective effects of whole grains and wholegrain foods towards the development of chronic diseases could be mediated via their beneficial effect on weight control through the promotion of satiety and enhancement of satiation (28) . In the present study, higher wholegrain products intake was associated with lower BMI, which is comparable to findings from other crosssectional studies (18)(19)(20)(21) . Also, risk of obesity or abdominal obesity has cross-sectionally been reported to be lower among persons with high intakes of whole grains compared with persons with low intakes (25) .…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, the protective effects of whole grains and wholegrain foods towards the development of chronic diseases could be mediated via their beneficial effect on weight control through the promotion of satiety and enhancement of satiation (28) . In the present study, higher wholegrain products intake was associated with lower BMI, which is comparable to findings from other crosssectional studies (18)(19)(20)(21) . Also, risk of obesity or abdominal obesity has cross-sectionally been reported to be lower among persons with high intakes of whole grains compared with persons with low intakes (25) .…”
Section: Discussionsupporting
confidence: 92%
“…However, others did not find this association (Pietinen et al, 1996;Wu et al, 2003). Van de Vijver et al (2009) found an inverse association between whole grain and BMI, but the inverse association between DF intake and BMI was present only in men. In addition, an increase in BMI was found to be a strong predictor of mild, moderate and severe progression of carotid IMT, but not for others clinical marker of atherosclerosis (carotid plaques, aortic atherosclerosis or braquial-ankle index) (Van der Meer et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Harnack et al (49) has shown that RTEC is an important food source of whole grains which have been found (50,51) to be inversely associated with obesity, and that cereals and cereal products are the main sources of dietary fibre (4) with an undoubtedly positive effect on BMI status (36,52) . Thus, these findings suggest that additional components in whole grains may contribute to favourable metabolic alterations that may reduce long-term weight gain (31) , providing another possible explanation of the observed associations.…”
Section: Possible Explanations For the Observed Associationsmentioning
confidence: 99%